Spiritual intelligence and its relationship to psychological flow as predictors of psychological quality of life for secondary school teachers in Riyadh - Al-Quraini, Hessa Fahd; Al-Mutairi, Siham Mahji (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the relationship between the concept of spiritual intelligence and psychological flow as predictors of the quality of psychological life of Riyadh phase teachers, and relied on a descriptive and analytical approach. The study sample consisted of 377 female core teachers from the Riyadh region. She was based on her concept of spiritual intelligence, her psychological flow scale, and her quality of psychological life scale. The results of the study revealed a statistically significant correlation between spiritual intelligence and psychological flow for a sample of secondary school teachers in Riyadh. In addition to a statistically significant correlation between spiritual intelligence and psychological quality of life for a sample of secondary school teachers in Riyadh, there was also a statistically significant correlation between psychological flow and psychological quality of life for a sample of the high school teachers in Riyadh, which led to the possibility of predicting quality of life through spiritual intelligence and psychological flow in the minds of the high school teachers in Riyadh. The study recommended attention should be paid to developing skills and abilities of spiritual intelligence and flow psychological quality of psychological life for female teachers in the Kingdom of Arabia Saudi Arabia, conducting many studies and research on intelligence spiritual flow and the quality of psychological life in relation to many subjective factors for parameters and studies to identify the role of tasks of spiritual intelligence, psychological flow, psychological quality of life, and many spiritual and psychological approaches to coping with problems various, and conduct courses and workshops to develop spiritual intelligence and psychological flow and quality of psychological life.